Hsa_circ_0009361 acts as the sponge of miR-582 to suppress colorectal cancer progression by regulating APC2 expression. (30th May 2019) - Geng, Yiting; Zheng, Xiao; Hu, Wenwei; Wang, Qi; Xu, Yanjie; He, Wenting; Wu, Chen; Zhu, Danxia; Wu, Changping; Jiang, Jingting
Abstract : Circular RNA (circRNA) plays an important role in the development of human malignant tumors. Recently, an increasing number of circRNAs have been identified and investigated in various tumors. However, the expression pattern and biological function of circRNAs in colorectal cancer (CRC) still remain largely unexplored. In the present study, hsa_circ_0009361 was significantly down-regulated in CRC tissues and cells. Low expression level of hsa_circ_0009361 promoted the proliferation, epithelial–mesenchymal transition (EMT), migration, and invasion of CRC cells. Hsa_circ_0009361 was identified as the sponge of miR-582 by fluorescence in situ hybridization (FISH), RNA immunoprecipitation (RIP), and luciferase reporter assays. Overexpression of hsa_circ_0009361 up-regulated the expression of adenomatous polyposis coli 2 (APC2) and inhibited the activity of the Wnt/β-catenin pathway by competitively combining with miR-582. Exogenous miR-582 and APC2 interventions could reverse the multiple biological functions mediated by hsa_circ_0009361 in CRC cells. In vivo experiments also confirmed that hsa_circ_0009361 inhibited the growth and metastasis of CRC. Hsa_circ_0009361 acted as a tumor suppressive sponge of miR-582, which could up-regulate the expression of APC2, inhibit the Wnt/β-catenin signaling, and suppress the growth and metastasis of CRC. Collectively, the hsa_circ_0009361/miR-582/APC2 network could be employed as a potential therapeutic target for CRC patients.